IMPLEMENTASI STANDAR PROSES PENDIDIKAN DALAM MEWUJUDKAN PEMBELAJARAN EFEKTIF : STUDI MULTISITUS PADA SEKOLAH MENENGAH PERTAMA DI BALI - Friska Amalia; Ni Luh Winda Rianti; Ni Putu Dessy Wiranti; Ni Wayan Rati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the implementation of process standards in realizing effective learning at two junior high schools in Bali with different regional characteristics: an economic center area and an agricultural area. The method used is a qualitative approach with a multi-site study design to compare phenomena in Badung Regency and Jembrana Regency. Data were collected through participant observation, in-depth interviews, and documentation studies of teaching modules and school regulations. Data analysis was performed through reduction, display, and verification across sites. The results indicate that the implementation of process standards is carried out consistently through three main stages: (1) learning planning using a Backward Design flow to harmonize national regulations with local contexts; (2) learning implementation that is interactive and inspirational through the integration of cutting-edge technology and strategic partnerships ; and (3) learning assessment that has transformed into a reflective culture by involving student voice to build learning independence. The conclusion confirms that socio-geographic differences do not hinder educational quality but instead provide space for humanistic flexibility and adaptability within the learning ecosystem